Hizb al-Tahrir And the Arab-Israeli Wars - Harez, Wael Heraz; Abdul Hamid, Faisal @ Ahamad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2017)
This research represents the historical evolution of Hizb Al- Tahreer’s view of the Arab - Israeli conflict wars in the years following the emergence of the party; from the beginning of the fifties until the date of writing this research. This includes the pathway of the party, its analytical tools, and its vision of the solution of the problems those conflict wars had created. Before that, this research tries to set the headlines the party has declared as basic principles to deal with the Palestinian issue. Although Hizb Al-Tahreer has made the Khilafa or the Islamic ruling its central issue, the Palestinian conflict has taken a decent part of the thought of the party. However, the attitude of the party ended up being a talk only instead of supporting any actual liberation project